Zebrafish larvae: A new model to study behavioural effects and metabolism of fentanyl, in comparison to a traditional mice model. (July 2022) - Pesavento, S.; Bilel, S.; Murari, M.; Gottardo, R.; Arfè, R.; Tirri, M.; Panato, A.; Tagliaro, F.; Marti, M.
In an effort to find alternatives to study in vivo the so-called New Psychoactive Substances (NPS), the present work was undertaken to investigate the use of zebrafish larvae as animal model in pharmaco-toxicology, providing behavioural and metabolism information. For this purpose, fentanyl, the progenitor of an extremely dangerous group of NPS, was administered at different doses to zebrafish larvae (1, 10, 50, 100 µM) in comparison to mice (0.1, 1, 6, 15 mg/kg), as a well-established animal model. A behavioural assay was performed at the time of the peak effect of fentanyl, showing that the results in larvae are consistent with those observed in mice. On the other hand, several morphological abnormalities (namely yolk sac edema, abnormal pericardial edema, jaw defect and spinal curvature) were found in larvae mostly at high fentanyl doses (50, 100 µM). Larva extract and mice urine were analyzed by using liquid chromatography coupled to high resolution mass spectrometry to identify the metabolic pathways of fentanyl. The main metabolites detected were norfentanyl and hydroxyfentanyl in both the tested models. In conclusion, the present study provides evidence that fentanyl effects on zebrafish larvae and metabolism are similar to rodents and consequently support the hypothesis of using zebrafish larvae as a suitable rapid screening tool to investigate new drugs, and particularly NPS.